Estudio avifaunístico en el Barrio Valle Hermoso I y el Refugio de Vida Silvestre Pasochoa, Parroquia de Tambillo, Cantón Mejía, Provincia de Pichincha” - Arias Donoso, Hugo Eduardo (2018)
The present research work carried out between the neighborhood "Valle Hermoso" and the Pasochoa Wildlife Refuge, Tambillo parish, Mejía Canton, Pichincha Province, has as its main axis the identification of existing bird species in the area.Within the field research different methods, techniques and instruments were applied that allowed to develop the avifauna study in the area. For this, a situational diagnosis of the area was made, where the interview was used as a technique for observation of information; In addition, the field visits allowed us to obtain fundamental data to determine the ecosystem present in the area, knowing the altitudinal floor of the area, the tasks that are carried out, activities of the inhabitants and, above all, obtaining information on the flora and fauna. After knowing the environmental aspects, a study area was determined, based on the type of ecosystems according to the System of Classification of the Ecosystems of the Continental Ecuador denominated as: Montane evergreen forest of the north of the Eastern mountain range of the Andes. Where the birds were recorded by means of point counting and intensive search, 17 species, six orders and 13 families were registered, of which the most predominant order was the Passeriform, because this order is adaptable to any type of ecosystem since they have the facility of finding seeds, insects and fruits as food. In addition to this, there was an additional record of five species, three orders and five families outside the study area, which means that in other areas surrounding the study area there are different species of birds. Finally, the information was systematized through the design and elaboration of the Avifaunistic Guide, which contains taxonomic information of the birds, that is: order, family, gender and species. The document also has important information data, such as common names, in both Spanish and English; a small description of the bird is also detailed. The guide complies with the basic parameters of text contrast, clarity, sharpness of images and dimensions. These aspects facilitate the readers to have in their hands a document that allows the identification of the species of birds in the area, with contents of real images of the birds fulfilling the purpose of being a basic instrument of future research.